2012
DOI: 10.4172/2155-6121.s5-001
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Vitamin D Among Patients with Nasal Polyps in Bolu,Turkey

Abstract: Background: Nasal polyps are common chronic non-neoplastic growths of the nasal or paranasal sinus mucosa. Vitamin D deficiency, in particular, has been linked to a high rate of both infectious and inflammatory diseases, including those of the upper and lower airways. Aim:In this study, we analyzed the association between plasma 25-hydroxy vitamin D (25[OH]D) levels in patients with nasal polyps. Material and method:Sixty patients (31 male and 29 female), whose ages ranged from 18 to 55 years, were enrolled in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
2
1
0
Order By: Relevance
“…The present study revealed that gender and age in all the four groups had no effect on Vitamin D levels. This is consistent with the findings of Apuhan et al 33 One study found that older adults are at higher risk for Vitamin D deficiency. 34 This may be due to a reduced ability of the skin to produce enough vitamin D and a reduced ability to absorb vitamin D from food.…”
Section: Discussionsupporting
confidence: 93%
“…The present study revealed that gender and age in all the four groups had no effect on Vitamin D levels. This is consistent with the findings of Apuhan et al 33 One study found that older adults are at higher risk for Vitamin D deficiency. 34 This may be due to a reduced ability of the skin to produce enough vitamin D and a reduced ability to absorb vitamin D from food.…”
Section: Discussionsupporting
confidence: 93%
“…Also the nasal polyps before VD taking in the present study showed damage of respiratory epithelium that rests on thick basal lamina with numerous inflammatory cells infiltration, extensive accumulation of collagen fibers in lamina propria and highly expressed TLR-9 and these results were agreed with [23][24][25] who reported that the histological appearance of NP is characterized by respiratory epithelium with a range of mucosal alterations that include ulceration, thickening of the basement membrane, near normal nasal mucosa with overcrowded respiratory epithelium rests on apparently thin basal lamina and lamina propria of loose connective tissue with few cells infiltration and many blood vessels and showed significant decrease (P<0.05) in all symptoms of VAS score and endoscopic appearance of Lund and Mackey score and the mean area % of submucosal accumulation of collagen fibers and TLR-9 expression while this decrease was insignificant (P < 0.05) in the low dose VD group (IIa). These results agreed with [39] who reported that the antiproliferative effects of VD were dose-and timedependent, the lower concentration used was mostly without any effect and [40] stated that in the overall study population of Finnish VD Study, clinical outcomes appeared to favor the high-dose VD group. Also Allen et al, reported that high dose VD (5000-10,000 IU/day) has immunomodulatory and anti-inflammatory effects through increasing interleukin-10 (IL-10) production by peripheral blood mononuclear cells and a reducing frequency of T helper 17 cells (Th17) cells and Kimball et al, reported that high doses of VD may be required for therapeutic efficacy and tolerability.…”
Section: Discussionsupporting
confidence: 81%
“…On the other hand, in their studies, Apuhan et al [9] could not prove any association between serum VD3 level and CRSwNP. Another study showed the circulating levels of 25-OH-VD3 were equivalent between patients with CRSwNP and control [10] .…”
Section: Discussionmentioning
confidence: 75%